Pre-diagnostic plasma bile acid levels and colon cancer risk: a prospective study - Tilman, K; Stepien, M; López-Nogueroles, M; Damms Machado, A; Sookthai, D; Johnson, T; Roca, M; Hüsing, A; González Maldonado, S; Cross, AJ; Murphy, N; Freisling, H; et al. (Oxford University Press, 2019)
Background Bile acids have been proposed to promote colon carcinogenesis. However, there are limited prospective data on circulating bile acid levels and colon cancer risk in humans. Methods Associations between pre-diagnostic plasma levels of 17 primary, secondary and tertiary bile acid metabolites (conjugated and unconjugated) and colon cancer risk were evaluated in a nested case-control study within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Bile acid levels were quantified by tandem mass spectrometry in samples from 569 incident colon cancer cases and 569 matched controls. Multivariable logistic regression analyses were used to estimate odds ratios (ORs) for colon cancer risk across quartiles of bile acid concentrations. Results Positive associations were observed between colon cancer risk and plasma levels of 7 conjugated bile acid metabolites, i.e. primary bile acids glycocholic acid (ORQuartile 4 vs. Quartile 1=2.22,95 % confidence interval[CI]=1.52, 3.26), taurocholic acid (OR = 1.78, 95%CI=1.23, 2.58), glycochenodeoxycholic acid (OR = 1.68, 95%CI=1.13, 2.48), taurochenodeoxycholic acid (OR = 1.62, 95%CI=1.11-2.36), and glycohyocholic acid (OR = 1.65, 95%CI=1.13, 2.40) as well as the secondary bile acids glycodeoxycholic acid (OR = 1.68, 95%CI=1.12, 2.54) and taurodeoxycholic acid (OR = 1.54, 95%CI=1.02, 2.31). By contrast, unconjugated bile acids and tertiary bile acids were not associated with risk. Conclusions This prospective study showed that pre-diagnostic levels of certain conjugated primary and secondary bile acids were positively associated with risk of colon cancer. Our findings support experimental data to suggest that a high bile acid load is colon cancer promotive.